Pengaruh Hypnosis Lima Jari Terhadap Burnout pada Perawat di Ruang Isolasi Covid-19 - Anak Agung Ayu Mirahadi; Ni Made Nopita Wati; Ika Setya Purwanti (LPPM STIKES Guna Bangsa, 2022)
The Covid-19 pandemic is the biggest challenge to the health care system in the word today. Nurses as one of the medical personnel who are fighting at the forefront in fighting the Covid-19, face various problems such as an increase in workload and a psychological burden when caring for patients during the Covid-19. The high workload and the heavy psychological burden borne by nurses in caring for patients during the Covid-19, make nurses vulnerable to burnout. Burnout experienced by nurses when caring for patients caring for pateints during the Covid-19 pandemic. Burnout experienced by nurses when caring for patients during the Covid-19 pandemic is called pandemic burnout. Non-pharmacological therapy is expected to reduce burnout in nurses. Five-finger hypnosis is one of the most efeective non-pharmacological therapies to reduce one’s stress and anxiety. This study aims to determine the effect of five-finger hypnosis on burnout in nurses in the Covid-19 isolation room. This research uses pre-experimental research, with a one group pre-post test design. Sample in this study amounted to 22 people who werw selected through purposive sampling technique. Data was collected using a burnout pandemic questionnaire. The results of the study were analyzed using the Wilcoxon Sign Rank Test. The results showed that before the intervention was given, most of the respondents experienced high burnout as many as 11 people (50%) shile after being given the intervention there was a decrease where most of the respondents experienced moderate burnout as many as 13 people (59,1%) with p value 0,000.